Prevalence and Lipid Profile Associations of Elevated Lipoprotein(a) Among Indonesian Adults: A Cross-Sectional Study - Jason Wirandy Haryanto; Kevin Jonatan Sandi; Surya Sinaga Immanuel; Angely Christie Rumayar; Leonardo Paskah Suciadi (The Indonesian Heart Association, 2026)
Background: Lipoprotein(a) [Lp(a)] is a genetically determined lipoprotein and an independent risk factor for Atherosclerotic Cardiovascular Disease (ASCVD). While 20–30% of adults worldwide have elevated Lp(a), data from Indonesia remain scarce. Given reported differences by sex and metabolic profile, this cross-sectional study aimed to determine the prevalence of elevated Lp(a) and its associations with lipid parameters and Hemoglobin A1c (HbA1c) among adults undergoing routine health screening at a tertiary hospital in Indonesia. Methods: This cross-sectional study analyzed data from 904 adults who underwent routine health screening at Siloam Hospitals Kebon Jeruk, Jakarta (2021–2024). Data on Lp(a), lipid profile, and HbA1c were extracted from the medical records. The normality of data was assessed using the Shapiro–Wilk test. Group comparisons were performed using the Mann–Whitney U test, and correlations between log-transformed Lp(a) and metabolic parameters were evaluated using Spearman correlation and simple linear regression. Results: Among 904 participants, 18.8 % had elevated Lp(a) levels (> 30 mg/dL). Females showed significantly higher Lp(a) concentrations than males (p = 0.008). Low-Density Lipoprotein Cholesterol (LDL-C) levels were slightly higher in participants with elevated Lp(a) but did not differ significantly (p = 0.19). On linear regression, LDL-C was positively associated with log-transformed Lp(a) (B = 0.002, p < 0.001), whereas triglycerides were inversely associated (B = −0.001, p = 0.029); no significant relationships were observed for High-Density Lipoprotein Cholesterol (HDL-C) or HbA1c. Conclusion: Nearly one in five adults undergoing routine health screening in this Indonesian cohort had elevated Lp(a) levels. Females exhibited significantly higher Lp(a) concentrations than males, and LDL-C showed a modest positive association with Lp(a). These findings reinforce the relevance of Lp(a) as an important, genetically influenced cardiovascular risk marker and support routine Lp(a) screening for improved risk stratification in clinical practice.